Sometimes I am worried for sharing and talking - Paruit, Marie; Rose, Janet (London campbell books, 2020)
Sometimes I am Worried helps young children to start managing their emotions. They can lift the flaps, slide the tabs and turn the wheel to explore what a worry is, why they might worry and how they can stop their worries from becoming too big. With delightful illustrations from Marie Paruit on every page, this is the perfect book for parents and carers to share with young children who may be anxious about something and to develop their emotional intelligence. Explanations, hints and tips from Early Years expert Dr Janet Rose will provide parents with all the extra guidance they need
Education
1 23
Keywords: Educational psychology